Implementasi Pencarian Link graph terbaik dalam menentukan Kalimat Representatif Pada Peringkasan Dokumen Berbahasa Indonesia - Irwan Darmawan; Sholeh Rachmatullah; Nilam Ramadhani (LPPM STIKOM Tunas Bangsa, 2023)
Indonesian documents have many or several sentences that are considered important in summarizing one document or many documents, sentences that appear a lot in documents are usually considered important sentences or reflect representative sentences on a document, even though these are not necessarily sentences that should be taken and put into representative sentences in determining the summarization of documents. In the link graph method used, it can indeed determine the amount of sentence weight in each sentence, it becomes a problem when sentence cutting is done if it is considered to have a very small weight. So a solution is needed to overcome this, namely by finding or determining the best parameters on the link graph of each sentence in the document summary. The value of such parameters is used to determine the truncation of each sentence. If the weight value of the sentence does not reach the limit of the parameter to be searched then the sentence is not included in the sentence processing in determining the summary of the document. The test parameters used are lambda i.e. (0.1, 0.3, 0.5) and for dumping factor i.e. (0.3, 0.5, 0.8)